Resin material for solid-state battery, resin material, resin material composition for solid electrolyte, sheet material and battery
By using a resin material with a main chain derived from norbornene in the solid electrolyte material and introducing ethylene oxide and ester structures into its side chains, the problem of unstable ionic conductivity of existing materials when temperature changes is solved, and high ionic conductivity and performance stability over a wide temperature range are achieved.
Patent Information
- Application Number
- JP2023181478
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-05-02
AI Technical Summary
The ionic conductivity of existing solid electrolyte materials is unstable when the temperature changes, resulting in rapid changes in the ionic conductivity of the battery within the operating temperature range.
A resin material with a main chain derived from norbornene, whose side chains contain ethylene oxide structures and ester structures, and a combination of these structures is used to improve the temperature stability and ionic conductivity of the material.
It realizes the high ionic conductivity that maintains stable over a wide temperature range, reduces the problem of a sharp decrease in ionic conductivity of the material at low temperatures, and improves the reliability and performance stability of the battery.
Smart Images

Figure 2025070879000017 
Figure 2025070879000001 
Figure 2025070879000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin material for solid state batteries, a resin material, a resin material composition for solid electrolytes, a sheet material, and a battery. [Background technology]
[0002] For example, liquid electrolytes have been used in secondary batteries such as lithium ion secondary batteries, etc. However, the use of liquid electrolytes raises concerns about leakage from product containers, and improvements have been required to increase reliability.
[0003] In order to solve these problems, a method of using a solid electrolyte instead of a liquid electrolyte has been considered, but there is a problem that the ionic conductivity is lower than that of a liquid electrolyte.
[0004] In order to solve such problems, there have been attempts to use polyethylene oxide as a polymer for the electrolyte (see, for example, Patent Document 1).
[0005] However, when polyethylene oxide is used, although it shows a relatively high ionic conductivity in the high temperature range, there is a problem that the ionic conductivity drops rapidly when the temperature drops. Thus, when the temperature dependency of the ionic conductivity becomes large, there is a problem that the ionic conductivity changes rapidly within the operating temperature range of the battery. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2014 / 002858 Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a resin material and a resin material for solid-state batteries that exhibit stable and excellent ionic conductivity over a wide temperature range, and to provide a resin material composition for solid electrolytes, a sheet material, and a battery that contain the resin material for solid-state batteries. [Means for solving the problem]
[0008] These objects can be achieved by the present invention described below in (1) to (13). (1) The main chain has a structure derived from norbornene, A resin material for a solid-state battery, comprising an ethylene oxide structure in a side chain, and an ester structure provided between the norbornene-derived structure and the ethylene oxide structure.
[0009] (2) The resin material for a solid battery according to the above (1), which contains a monomer component represented by the following formula (NB):
[0010] [ka] (In formula (NB), R 1 is a hydrogen atom or a hydrocarbon group, and R 2 , R 3 and R 4 are each independently a hydrogen atom or an organic group having 1 to 3 carbon atoms, m is an integer of 0 to 4, n is an integer of 1 or more, and a1 is 0, 1, or 2.
[0011] (3) The resin material for a solid battery according to the above (2), which contains a monomer component represented by the following formula [VI] in addition to the monomer component represented by the above formula (NB):
[0012] [ka] (In formula [VI], m is an integer of 0 or more and 4 or less.)
[0013] (4) The ratio of the monomer represented by the above formula (NB) in the resin material for solid-state batteries is X NB [mol%], the proportion of the monomer represented by the above formula [VI] is X VI When expressed as [mol%], 0.1 / 99.9≦X VI / X NB The resin material for a solid-state battery according to claim 3, which satisfies a relationship of ≦30 / 70.
[0014] (5) The resin material for a solid-state battery according to any one of (1) to (4) above, having a weight-average molecular weight of 100,000 or more and 500,000 or less.
[0015] (6) The resin material for a solid-state battery according to any one of (1) to (5) above, having an average degree of polymerization of 100 or more and 800 or less.
[0016] (7) The resin material for a solid-state battery according to any one of (1) to (6) above, having a softening point of −20° C. or higher and 100° C. or lower.
[0017] (8) A resin material comprising a monomer component represented by the following formula [VII]:
[0018] [ka] (In formula [VII], n is 4 or 5.)
[0019] (9) A resin material composition for a solid electrolyte, comprising the resin material for a solid battery according to any one of (1) to (7) above and a lithium salt.
[0020] (10) The resin material composition for solid electrolytes according to the above (9), wherein the lithium salt is at least one selected from the group consisting of LiSCN, LiN(CN)2, LiClO4, LiBF4, LiAsF6, LiPF6, LiCF3SO3, Li(CF3SO2)2N, Li(CF3SO2)3C, LiSbF6, Li(FSO2)2N, LiC4F9SO3, LiN(SO2CF2CF3)2, LiPF3(CF2CF3)3, LiPF3(C2F5)3, LiPF3(CF3)3, LiCl, LiF, LiBr, LiI, LiB(C2O4)2, lithium difluoro(oxalate)borate and lithium bis(oxalate)borate.
[0021] (11) A resin material composition for solid electrolytes according to the above (9) or (10), wherein a ratio of the total number of oxygen atoms contained in the resin material for solid batteries contained in the resin material composition for solid electrolytes to the total number of lithium atoms contained in the lithium salt contained in the resin material composition for solid electrolytes is 4.0 or more and 33.3 or less.
[0022] (12) A sheet material comprising a material containing the resin material for a solid-state battery according to any one of (1) to (7) above.
[0023] (13) a positive electrode layer; A negative electrode layer; a battery comprising an electrolyte layer located between the positive electrode layer and the negative electrode layer, A battery comprising the resin material for a solid battery according to any one of (1) to (7) above. Effect of the Invention
[0024] According to the present invention, it is possible to provide a resin material and a resin material for solid-state batteries that exhibit stable and excellent ionic conductivity over a wide temperature range, and also to provide a resin material composition for solid electrolytes, a sheet material, and a battery that contain the resin material for solid-state batteries. [Brief description of the drawings]
[0025] [Figure 1] FIG. 1 is a longitudinal sectional view illustrating a schematic diagram of an example of an all-solid-state battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The present invention will now be described in detail with reference to the accompanying drawings. [1] Resin material The resin material of the present invention exhibits stable and excellent ionic conductivity over a wide temperature range.
[0027] The resin material of the present invention is suitable for applications requiring excellent ion conductivity, and is particularly suitable for applications requiring stable and excellent ion conductivity over a wide temperature range.
[0028] Examples of resin materials that require the above-mentioned properties include components of solid-state batteries, specifically, resin materials for solid-state batteries, and binders (e.g., binders that have the function of bonding active material particles together, binders that bond a current collector and an active material layer, etc.).
[0029] In the following description, a resin material used as a constituent component of a solid-state battery is referred to as a resin material for a solid-state battery, and a resin material used as a solid electrolyte is referred to as a resin material for a solid electrolyte.
[0030] In the present invention, the solid electrolyte is a concept including all-solid electrolytes, semi-solid electrolytes, and gel electrolytes, and may contain a liquid component or an electrolytic solution in addition to a resin material for a solid electrolyte.
[0031] Hereinafter, a resin material for solid-state batteries will be mainly described as an example of the resin material of the present invention, but the applications of the resin material of the present invention are not limited thereto.
[0032] The resin material for a solid battery of the present invention has a norbornene-derived structure in its main chain, and has an ethylene oxide structure and an ester structure provided between the norbornene-derived structure and the ethylene oxide structure in its side chain.
[0033] This makes it possible to provide a resin material for solid-state batteries that exhibits stable and excellent ion conductivity over a wide temperature range. Such excellent effects are believed to be obtained for the following reasons. That is, by having an ethylene oxide structure, high ion conductivity is ensured, while by having the ethylene oxide structure in the side chain bonded to the norbornene-derived main chain structure, crystallization that is likely to occur with the ethylene oxide structure alone can be suppressed. As a result, it is believed that stable and excellent ion conductivity can be exhibited over a wide temperature range. In addition, by providing an ester structure between the norbornene-derived structure and the ethylene oxide structure, the norbornene-derived structure and the ethylene oxide structure can be separated, and the effect of having the ethylene oxide structure as described above can be significantly exhibited. In addition, by providing an ester structure between the norbornene-derived structure and the ethylene oxide structure, when a non-aqueous solvent is used in the preparation of the electrolyte membrane, the resin material for solid-state batteries exhibits good solubility in the non-aqueous solvent. In addition, by having a rigid norbornene-derived structure in the main chain, the resin material for solid-state batteries can obtain good mechanical properties when molded into, for example, a film. In addition, the heat resistance of the resin material for solid-state batteries can be made excellent. As a result, for example, it is possible to effectively prevent the resin material for solid-state batteries from being decomposed and generating gas due to heat treatment during the manufacturing process of the batteries.
[0034] Furthermore, the resin material for solid-state batteries can have excellent adhesion to inorganic materials (such as inorganic solid electrolytes, active materials, and current collectors, which will be described later).
[0035] In general, oxide-based inorganic solid electrolytes have high ionic conductivity but high interfacial resistance, and therefore require high-temperature treatment such as sintering to reduce the interfacial resistance. However, by combining the oxide-based inorganic solid electrolyte with the resin material for solid-state batteries of the present invention, the interfacial resistance can be reduced without high-temperature treatment such as sintering, and a flexible composite sheet with high ionic conductivity can be suitably formed.
[0036] Furthermore, unless high-temperature treatment such as sintering is performed on an oxide-based inorganic solid electrolyte, the interfacial resistance between the oxide-based inorganic solid electrolyte and the electrode material increases, causing problems with charging and discharging, but by combining the oxide-based inorganic solid electrolyte with the resin material for solid batteries of the present invention, the oxide-based inorganic solid electrolyte can be suitably bonded to the electrode without high-temperature treatment such as sintering, and good charging and discharging characteristics can be obtained. For the reasons described above, the charging and discharging characteristics, reliability, etc. of a battery made of a material containing the resin material for solid batteries can be made excellent.
[0037] The resin material for a solid-state battery of the present invention has a norbornene-derived structure in the main chain. An example of the norbornene-derived structure is a structure represented by the following formula [II] as a monomer.
[0038] [ka] (At least one of R1, R2, R3, R4, R5, R6, R7, R8, R9, and R10 in formula [II] is a single bond (direct bond) or a divalent atom or atomic group bonded to the side chain, and the rest are monovalent atoms or atomic groups.)
[0039] The divalent atomic group may, for example, be a linear or branched alkylene group. The monovalent atom includes, for example, a hydrogen atom. Examples of the monovalent atomic group include hydrocarbon groups such as alkyl groups, alkenyl groups, and alkynyl groups, and further include structures in which these are bonded to the divalent atom or divalent atomic group.
[0040] In particular, in the norbornene-derived structure, only one of R1 to R10 in the above formula [II] is a single bond bonded to the side chain, and the remaining nine are preferably hydrogen atoms.
[0041] This makes it possible to more significantly exhibit the effects of the present invention as described above. In addition, the synthesis of the monomer, which is the raw material of the resin material for solid-state batteries, can be performed in a higher yield, and the polymerization reaction of the monomer can also proceed more efficiently, thereby increasing the yield of the resin material for solid-state batteries of the present invention.
[0042] In this case, the single bond bonded to the side chain is preferably any one of R3 to R6 in the above formula [II].
[0043] This allows the effects of the present invention to be more pronounced as described above. In addition, the synthesis of the monomers that are the raw materials of the resin material for solid-state batteries can be performed in a higher yield, and the polymerization reaction of the monomers can be made to proceed more efficiently, so that the yield of the resin material for solid-state batteries of the present invention can be further increased.
[0044] When the resin material for a solid battery of the present invention contains a structure represented by the above formula [II] as a norbornene-derived structure, the resin material for a solid battery of the present invention may contain, in a molecule, a plurality of different structures among the structures represented by the above formula [II].
[0045] The resin material for a solid-state battery of the present invention has an ethylene oxide structure in the side chain. In the present invention, the ethylene oxide structure is -(CH2CH2O) n - (where n is an integer of 1 or greater).
[0046] The ethylene oxide structure may be a single one (one that does not have a structure in which ethylene glycol molecules are condensed together) or may have a repeating structure (one that has a structure in which ethylene glycol molecules are condensed together), but it is preferable that it has a repeating structure (one that has a structure in which ethylene glycol molecules are condensed together). In other words, -(CH2CH2O) n It is preferable that n is an integer of 2 or more. This makes it possible to increase the ionic conductivity of the resin material for solid state batteries.
[0047] When the ethylene oxide structure constituting the side chain of the resin material for a solid battery of the present invention has a repeating structure (having a structure in which ethylene glycol molecules are condensed with each other), the number of ethylene glycol molecules in the ethylene oxide structure (-(CH2CH2O) n The value of n is preferably 2 or more and 6 or less, more preferably 2 or more and 5 or less, and even more preferably 2 or more and 3 or less.
[0048] This allows the effects of the present invention to be more pronounced as described above, and also improves the stability and ease of handling of the sheet when processed into a sheet material as described below.
[0049] The resin material for a solid-state battery of the present invention may contain, in a molecule, a plurality of types of structures having different numbers of condensation of ethylene glycol molecules.
[0050] The resin material for a solid-state battery of the present invention has an ester structure in addition to the above-mentioned ethylene oxide structure in a side chain, and this ester structure is provided between the norbornene-derived structure and the ethylene oxide structure.
[0051] The ester structure may not be directly bonded to the ethylene oxide structure, and at least one atom may be interposed between the ester structure and the ethylene oxide structure, but it is preferably directly bonded to the ethylene oxide structure.
[0052] This makes it easier to form a crown ether with an ethylene oxide structure, which makes it easier to dissociate ions, and further improves ion conductivity.
[0053] Hereinafter, the case where the ethylene oxide structure and the ester structure are directly bonded in the side chain will be mainly described.
[0054] The resin material for a solid-state battery of the present invention may have the ethylene oxide structure and the ester structure in a side chain, and the side chain may further have another partial structure, for example, a partial structure provided between the main chain and the ester structure, a partial structure provided between the ester structure and the ethylene oxide structure, a partial structure provided on the end side of the ethylene oxide structure opposite to the end side of the ester structure, etc.
[0055] The partial structure provided between the main chain and the ester structure includes, for example, an alkylene group.
[0056] Examples of the partial structure provided on the end side of the ethylene oxide structure opposite to the end side of the ester structure include a hydrogen atom, an alkyl group, and an alkylene group.
[0057] The resin material for a solid battery of the present invention has the ethylene oxide structure and the ester structure in a side chain, and may have a plurality of partial structures including the ethylene oxide structure and the ester structure in the side chain. In other words, for example, the side chain constituting the resin material for a solid battery of the present invention may have a first partial structure including the ethylene oxide structure and the ester structure, and a second partial structure including the ethylene oxide structure and the ester structure, which is provided on the terminal side (opposite side to the main chain) of the first partial structure.
[0058] When the resin material for a solid battery of the present invention has a plurality of side chains, it is sufficient that at least one of the side chains has a partial structure containing an ester structure and an ethylene oxide structure as described above, and a plurality of the side chains may have a partial structure containing an ester structure and an ethylene oxide structure as described above.
[0059] The resin material for a solid-state battery of the present invention may have a norbornene-derived structure in its main chain, an ethylene oxide structure in its side chain, and an ester structure provided between the norbornene-derived structure and the ethylene oxide structure. It is preferable that the resin material for a solid-state battery of the present invention contains a monomer component represented by the following formula (NB):
[0060] [ka] (In formula (NB), R 1 is a hydrogen atom or a hydrocarbon group, and R 2 , R 3 and R 4 are each independently a hydrogen atom or an organic group having 1 to 3 carbon atoms, m is an integer of 0 to 4, n is an integer of 1 or more, and a1 is 0, 1, or 2.
[0061] This allows the effects of the present invention to be more pronounced, as described above, and also improves the stability and ease of handling of the sheet when processed into a sheet material, as described below.
[0062] In the above formula (NB), m may be an integer of 0 or more and 4 or less, preferably an integer of 0 or more and 2 or less, and more preferably 0 or 2.
[0063] This allows the effects of the present invention to be more pronounced, as described above, and also improves the stability and ease of handling of the sheet when processed into a sheet material, as described below.
[0064] R in the above formula (NB) 1 may be a hydrogen atom or a hydrocarbon group, but is preferably an alkyl group having 1 to 4 carbon atoms, and more preferably a methyl group.
[0065] This allows the effects of the present invention to be more pronounced, as described above, and also improves the stability and ease of handling of the sheet when processed into a sheet material, as described below.
[0066] R in the above formula (NB) 2 , R 3 and R 4 may each independently be a hydrogen atom or an organic group having 1 to 3 carbon atoms, and is preferably a hydrogen atom.
[0067] This allows the effects of the present invention to be more pronounced as described above, and also improves the stability and ease of handling of the sheet when processed into a sheet material as described below.
[0068] As described above, the resin material for a solid-state battery of the present invention preferably contains a monomer component represented by the above formula (NB). Among the monomer components represented by the above formula (NB), it is preferable to contain a monomer component represented by the following formula [I]:
[0069] [ka] (In formula [I], m is an integer of 0 or more and 4 or less, n is an integer of 4 or more and 10 or less, and R 1 is a hydrogen atom or a hydrocarbon group.
[0070] This allows the above-mentioned effects of the present invention to be more significantly exhibited, and also allows the ion conductivity of the resin material for solid-state batteries to be increased, and also allows the sheet to have better stability and easier handling when processed into a sheet material as described below.
[0071] In the above formula [I], m may be an integer of 0 or more and 4 or less, preferably an integer of 0 or more and 2 or less, and more preferably 0 or 2.
[0072] This allows the effects of the present invention to be more pronounced as described above, and also improves the stability and ease of handling of the sheet when processed into a sheet material as described below.
[0073] In the above formula [I], n may be an integer of 4 or more and 10 or less, and is more preferably 4 or 5.
[0074] This allows the effects of the present invention to be more pronounced, as described above, and also improves the stability and ease of handling of the sheet when processed into a sheet material, as described below.
[0075] R in the above formula [I] 1 may be a hydrogen atom or a hydrocarbon group, but is preferably an alkyl group having 1 to 4 carbon atoms, and more preferably a methyl group.
[0076] This allows the effects of the present invention to be more pronounced, as described above, and also improves the stability and ease of handling of the sheet when processed into a sheet material, as described below.
[0077] When the resin material for a solid battery of the present invention contains a monomer component represented by the above formula (NB), the resin material for a solid battery of the present invention may contain, in a molecule, a plurality of different monomer components among the monomer components represented by the above formula (NB).
[0078] The resin material of the present invention preferably contains a monomer component represented by the following formula [VII].
[0079] [ka] (In formula [VII], n is 4 or 5.)
[0080] This makes it possible to provide a resin material that exhibits stable and superior ion conductivity over a wider temperature range.
[0081] The resin material for a solid-state battery of the present invention may have a norbornene-derived structure in the main chain, and may have a structure not derived from norbornene (e.g., a monomer component other than the above formula [II]) in the main chain in addition to the norbornene-derived structure.
[0082] The proportion of the monomer component having a norbornene-derived structure in all monomer components constituting the main chain of the resin material for solid-state batteries of the present invention is preferably 95.0 mol % or more, more preferably 98.0 mol % or more, and even more preferably 100 mol %.
[0083] The resin material for a solid battery of the present invention preferably contains a monomer component represented by the following formula [VI] in addition to the monomer component represented by the above formula (NB).
[0084] [ka] (In formula [VI], m is an integer of 0 or more and 4 or less.)
[0085] This makes it possible to improve the affinity between the resin material for solid batteries of the present invention and the lithium salt, and also makes it easier to adjust the softening point of the resin material for solid batteries of the present invention. For example, it becomes easier to provide a solid electrolyte containing the resin material for solid batteries of the present invention with a more suitable hardness.
[0086] In the above formula [VI], m may be an integer of 0 or more and 4 or less, preferably an integer of 0 or more and 2 or less, and more preferably 0 or 2. This allows the above-mentioned effects of the present invention to be more pronounced.
[0087] When the resin material for a solid-state battery of the present invention contains a monomer component represented by the above formula [VI], the resin material for a solid-state battery of the present invention may contain, in a molecule, a plurality of different structures among the structures represented by the above formula [VI].
[0088] The ratio of the monomer represented by the above formula (NB) in the resin material for a solid battery of the present invention is X NB [mol%], the proportion of the monomer represented by the above formula [VI] is X VI When expressed as [mol%], 0.1 / 99.9≦XVI / X NB It is preferable to satisfy the relationship of ≦30 / 70, and 1.0 / 99.0≦X VI / X NB It is more preferable that the relationship satisfies ≦25 / 75, and 5.0 / 95.0≦X VI / X NB It is even more preferable to satisfy the relationship ≦20 / 80. This makes the above-mentioned effects more pronounced.
[0089] The proportion of the monomer component represented by the above formula [I] in all the monomer components constituting the resin material for solid-state batteries of the present invention is preferably 70.0 mol% or more and 99.9 mol% or less, more preferably 75.0 mol% or more and 99.0 mol% or less, and even more preferably 80.0 mol% or more and 95.0 mol% or less.
[0090] The weight average molecular weight of the resin material for a solid battery of the present invention is preferably 100,000 or more and 500,000 or less, more preferably 150,000 or more and 450,000 or less, and even more preferably 200,000 or more and 400,000 or less.
[0091] This makes it possible to achieve a higher level of compatibility between the ionic conductivity of the resin material for solid state batteries and the stability and ease of handling of the sheet when processed into a sheet material as described below.
[0092] The average degree of polymerization of the resin material for a solid battery of the present invention is preferably 100 or more and 800 or less, more preferably 200 or more and 700 or less, and even more preferably 300 or more and 600 or less.
[0093] This makes it possible to achieve a higher level of compatibility between the ionic conductivity of the resin material for solid state batteries and the stability and ease of handling of the sheet when processed into a sheet material as described below.
[0094] The softening point of the resin material for solid state batteries of the present invention is preferably from -20°C to 100°C, more preferably from -15°C to 95°C, and even more preferably from -10°C to 90°C.
[0095] This makes it possible to achieve a higher level of both the ionic conductivity of the resin material for solid state batteries and the stability and ease of handling of the sheet when processed into a sheet material as described below.
[0096] The softening point can be determined using TMA / SS6100 under the conditions of a temperature rise rate of 3° C. / min and a compression load of 30 mN. In the examples described later, the softening point was determined under such conditions.
[0097] [2] Resin material composition for solid electrolyte Next, the resin material composition for solid electrolytes of the present invention will be described.
[0098] The resin material composition for solid electrolytes of the present invention is characterized by containing the above-mentioned resin material for solid batteries of the present invention and a lithium salt.
[0099] This makes it possible to provide a resin material composition for a solid electrolyte, which contains a resin material for a solid battery that exhibits stable and excellent ion conductivity over a wide temperature range, and as a result, a solid electrolyte that exhibits stable and excellent ion conductivity over a wide temperature range can be formed.
[0100] When the resin material for a solid battery of the present invention has a lithium salt structure in the molecule, the resin material composition for a solid electrolyte of the present invention contains a lithium salt other than the resin material for a solid battery.
[0101] The content of the resin material for solid batteries of the present invention in the resin material composition for solid electrolytes of the present invention is not particularly limited, but the ratio of the resin material for solid batteries of the present invention to the total solid content of the resin material composition for solid electrolytes of the present invention is preferably 45 mass % or more and 90 mass % or less, more preferably 50 mass % or more and 88 mass % or less, and even more preferably 55 mass % or more and 85 mass % or less.
[0102] This makes it possible to provide a solid electrolyte formed using the resin material composition for a solid electrolyte with superior ionic conductivity.
[0103] The lithium salt contained in the resin material composition for solid electrolytes of the present invention is not particularly limited, but is preferably at least one selected from the group consisting of LiSCN, LiN(CN)2, LiClO4, LiBF4, LiAsF6, LiPF6, LiCF3SO3, Li(CF3SO2)2N, Li(CF3SO2)3C, LiSbF6, Li(FSO2)2N, LiC4F9SO3, LiN(SO2CF2CF3)2, LiPF3(CF2CF3)3, LiPF3(C2F5)3, LiPF3(CF3)3, LiCl, LiF, LiBr, LiI, LiB(C2O4)2, lithium difluoro(oxalate)borate, and lithium bis(oxalate)borate, and is more preferably Li(CF3SO2)2N.
[0104] This makes it possible to provide a solid electrolyte formed using the resin material composition for a solid electrolyte with superior ionic conductivity.
[0105] The content of the lithium salt in the resin material composition for solid electrolytes of the present invention is not particularly limited, but the ratio of the lithium salt to the total solid content of the resin material composition for solid electrolytes of the present invention is preferably 5 mass % or more and 55 mass % or less, more preferably 10 mass % or more and 50 mass % or less, and even more preferably 15 mass % or more and 45 mass % or less.
[0106] This makes it possible to provide a solid electrolyte formed using the resin material composition for a solid electrolyte with superior ionic conductivity.
[0107] The content ratio of the resin material composition for solid electrolytes of the present invention and the lithium salt in the resin material composition for solid electrolytes of the present invention is not particularly limited, but the ratio of the total number of oxygen atoms contained in the resin material for solid batteries of the present invention contained in the resin material composition for solid electrolytes of the present invention to the total number of lithium atoms contained in the lithium salt contained in the resin material composition for solid electrolytes of the present invention is preferably 4.0 or more and 33.3 or less, more preferably 4.5 or more and 25.0 or less, and even more preferably 5.0 or more and 20.0 or less.
[0108] This makes it possible to provide a solid electrolyte formed using the resin material composition for a solid electrolyte with superior ionic conductivity.
[0109] The resin material composition for a solid electrolyte of the present invention may further contain a resin material other than the resin material for a solid battery of the present invention described above. Hereinafter, such a resin material is also referred to as "other resin material".
[0110] Other resin materials include, for example, a resin material having a norbornene-derived structure in the main chain and an ester structure in the side chain but not an ethylene oxide structure in the side chain; a resin material having a norbornene-derived structure in the main chain and an ethylene oxide structure in the side chain but not an ester structure in the side chain; a resin material having a norbornene-derived structure in the main chain and an ester structure and an ethylene oxide structure in the side chain but not an ester structure in the side chain; a resin material having an ethylene oxide structure and an ester structure in the side chain but not an ester structure in the side chain; Other resin materials include, for example, PVDF (polyvinylidene fluoride), PTFE (polytetrafluoroethylene), PVF (polyvinyl fluoride), PVC (polyvinyl chloride), PVA (polyvinyl alcohol), polyvinyl acetate, polyacrylic acid, polyacrylamide, polystyrene sulfonic acid, and derivatives thereof, and in particular, polyethylene oxide, polyacrylic acid, polyacrylamide, and derivatives thereof.
[0111] However, the proportion of other resin materials in the total solid content of the resin material composition for solid electrolytes of the present invention is preferably 20 mass % or less, more preferably 10 mass % or less, and even more preferably 5 mass % or less.
[0112] The resin material composition for solid electrolytes of the present invention may further contain, for example, an active material such as a positive electrode active material or a negative electrode active material.
[0113] Examples of the positive electrode active material include LiCoO2, LiNiO2, LiMn2O4, Li2Mn2O3, and LiCr. 0.5 Mn 0.5 Examples of the positive electrode active material include fluorides such as LiFeF3, LiBH4, Li4BN3H, and the like. 10boron complex compounds such as boron fluoride complexes, iodine complex compounds such as polyvinylpyridine-iodine complexes, and nonmetallic compounds such as sulfur can also be used.
[0114] Examples of negative electrode active materials include Nb2O5, V2O5, TiO2, In2O3, ZnO, SnO2, NiO, ITO, AZO, GZO, ATO, FTO, and Li4Ti5O. 12 Examples of the negative electrode active material include metal oxides such as Li2Ti3O7, and metal sulfides. Examples of the negative electrode active material include metals and alloys such as Li, Al, Si, Si-Mn, Si-Co, Si-Ni, Sn, Zn, Sb, Bi, In, and Au, carbon materials such as graphite and hard carbon, and LiC 24 Alternatively, a material in which lithium ions are inserted between layers of a carbon material such as LiC6 may be used.
[0115] When the resin material composition for a solid electrolyte of the present invention contains a positive electrode active material, the resin material composition for a solid electrolyte can be suitably used for forming a positive electrode layer of a battery as described below, and when the resin material composition for a solid electrolyte of the present invention contains a negative electrode active material, the resin material composition for a solid electrolyte can be suitably used for forming a negative electrode layer of a battery as described below.
[0116] The resin material composition for solid electrolytes of the present invention may further contain, for example, an inorganic solid electrolyte.
[0117] Examples of inorganic solid electrolytes include LiLaZrO-based compounds, LiLaZrNbO-based compounds, LiLaZrTaO-based compounds, LiLaTaO-based compounds, LiLaTiO-based compounds, LiAlGePO-based compounds, LiAlTiPO-based compounds, LiPO-based compounds, LiSiO-based compounds, LiBO-based compounds, LiPS-based compounds, and LiPSCl-based compounds.
[0118] When the resin material composition for solid electrolytes of the present invention contains an inorganic solid electrolyte, the proportion of the inorganic solid electrolyte in the total solid content of the resin material composition for solid electrolytes of the present invention is preferably 10 mass % or more and 95 mass % or less, more preferably 15 mass % or more and 90 mass % or less, and even more preferably 20 mass % or more and 85 mass % or less.
[0119] This can provide the resin material composition for solid electrolytes with better strength and ion conductivity.
[0120] The resin material composition for solid electrolytes of the present invention may further contain, for example, a non-aqueous solvent used in the electrolyte solution.
[0121] Examples of the non-aqueous solvent include cyclic carbonates such as propylene carbonate (PC), ethylene carbonate (EC), and vinylene carbonate (VC); chain carbonates such as diethyl carbonate (DEC), dimethyl carbonate (DMC), and methyl ethyl carbonate (MEC); cyclic ethers such as tetrahydrofuran (THF), 2-methyl tetrahydrofuran (2MeTHF), and dioxolane (DOX); chain ethers such as dimethoxy ethane (DME) and diethoxy ethane (DEE); γ-butyrolactone (GBL), acetonitrile (AN), and sulfolane (SL). These non-aqueous solvents can be used alone or in combination.
[0122] When the resin material composition for solid electrolytes of the present invention contains a non-aqueous solvent, the proportion of the plasticizer in the total solid content of the resin material composition for solid electrolytes of the present invention is preferably 0.1 mass % or more and 90 mass % or less, more preferably 1 mass % or more and 85 mass % or less, and even more preferably 5 mass % or more and 80 mass % or less.
[0123] This can improve the ease of handling of the resin material composition for solid electrolytes, the ion conductivity, and the interface formation with the composite.
[0124] The resin material composition for solid electrolytes of the present invention may further contain a liquid component that is liquid at 25°C, for example.
[0125] This improves the ease of handling of the resin material composition for solid electrolytes, and allows the formation of a solid electrolyte to be more suitably carried out.
[0126] Examples of the liquid component include alcohols such as methanol, ethanol, isopropanol, butanol, octanol, and benzyl alcohol; esters such as ethyl acetate, butyl acetate, ethyl lactate, γ-butyrolactone, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, butyl butyrate, and methyl benzoate; dioxane, 1,2-dimethoxyethane, tetrahydrofuran (THF), ethylene glycol monobutyl ether, propylene glycol monomethyl ether, ethylene diglycol monomethyl ether, ethylene diglycol ether, and the like. Examples of suitable ethers include ethers such as ethyl methyl ether; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, isobutyl ketone (DIBK), and cyclohexanone; nitriles such as acetonitrile; aromatic hydrocarbons such as benzene, toluene, xylene, trimethylbenzene (mesitylene, hemimelitene, pseudocumene), ethylbenzene, and tetralin, as well as derivatives thereof (for example, compounds in which the hydrogen atoms of these compounds are substituted with other atoms or atomic groups (functional groups, etc.)), and one or more selected from these may be used in combination.
[0127] When the resin material composition for solid electrolytes of the present invention contains the liquid component, the proportion of the liquid component in the resin material composition for solid electrolytes of the present invention is preferably 0.001% by mass or more and 10% by mass or less, and more preferably 0.005% by mass or more and 5% by mass or less.
[0128] This makes it possible to more suitably remove liquid components during the formation of the solid electrolyte while improving the ease of handling of the resin material composition for solid electrolytes, thereby improving the productivity of the solid electrolyte.
[0129] The resin material composition for solid electrolytes of the present invention may contain components other than the above-mentioned components. Hereinafter, such components are also referred to as "other components".
[0130] Examples of other components include adhesion aids, leveling agents, defoamers, colorants, antioxidants, flame retardants, inorganic fillers such as silica, medium-chain normal alkanes such as paraffin and petrolatum, natural materials such as rosin, pine resin, and Canada balsam, and glymes such as butyl glyme and tetraglyme.
[0131] However, the proportion of other components in the resin material composition for solid electrolytes of the present invention is preferably 10 mass % or less, more preferably 5 mass % or less, and even more preferably 3 mass % or less.
[0132] [3] Sheet material Next, the sheet material of the present invention will be described.
[0133] The sheet material of the present invention is characterized in that it is made of a material containing the above-mentioned resin material for a solid-state battery of the present invention.
[0134] This makes it possible to provide a sheet material containing a resin material for solid-state batteries that exhibits stable and excellent ion conductivity over a wide temperature range. In addition, by using such a sheet material, a layered (sheet-shaped) solid electrolyte can be suitably formed. As a result, it can be suitably applied to the manufacture of a battery as described below. More specifically, when the sheet material does not contain an active material, it can be suitably used to form a solid electrolyte layer of a battery, when the sheet material contains a positive electrode active material, it can be suitably used to form a positive electrode layer of a battery, and when the sheet material contains a negative electrode active material, it can be suitably used to form a negative electrode layer of a battery.
[0135] The content of the resin material for solid-state batteries of the present invention in the sheet material of the present invention is preferably 45% by mass or more and 90% by mass or less, more preferably 50% by mass or more and 88% by mass or less, and even more preferably 55% by mass or more and 85% by mass or less.
[0136] This makes it possible to provide a solid electrolyte formed using the resin material composition for a solid electrolyte with superior ionic conductivity.
[0137] The sheet material of the present invention may contain components other than the resin material for a solid-state battery of the present invention. Examples of such components include the components described in the resin material composition for solid electrolytes.
[0138] The thickness of the sheet material of the present invention is not particularly limited, but is preferably from 5 μm to 5000 μm, and more preferably from 10 μm to 1000 μm.
[0139] This makes it easier for the sheet material itself to maintain its mechanical strength in a more suitable manner, making it easier to handle the sheet material during the battery manufacturing process and the like.
[0140] The sheet material of the present invention may be produced by any method, but can be suitably produced, for example, by the following method.
[0141] That is, a composition containing the constituent materials of the sheet material or precursors thereof can be formed into a sheet to obtain the sheet material.
[0142] Examples of the precursor of the constituent material of the sheet material that can be contained in the composition include oligomers and prepolymers corresponding to the above-mentioned resin material for solid-state batteries of the present invention and other resin materials.
[0143] The sheet material can be produced using the above-mentioned resin material composition for solid electrolytes. When a composition containing a liquid component is used to manufacture a sheet material, for example, an excess amount of the liquid component may be used when preparing the composition, and a portion of the liquid component may be removed before forming the composition into a sheet to form a slurry.
[0144] When a sheet material is produced using a composition containing a liquid component, for example, a layer is formed using various coating methods such as cast coating, and then the liquid component is removed from the layer, thereby making it possible to obtain a suitable sheet material.
[0145] In addition, a part of the liquid component used in the manufacturing process may remain in the sheet material, and in such a case, the liquid component may be removed during the manufacturing process of the battery.
[0146] [4]Battery Next, the battery of the present invention will be described.
[0147] The battery of the present invention is a battery including a positive electrode layer, a negative electrode layer, and an electrolyte layer located between the positive electrode layer and the negative electrode layer, and is characterized in that it contains the above-mentioned resin material for solid batteries of the present invention.
[0148] This makes it possible to provide a battery containing a resin material for solid state batteries that exhibits stable and excellent ionic conductivity over a wide temperature range, thereby providing a battery that exhibits stable and excellent charge / discharge characteristics over a wide temperature range and has excellent reliability.
[0149] Hereinafter, among batteries, a representative description will be given of an all-solid-state battery as a secondary battery in particular.
[0150] FIG. 1 is a vertical cross-sectional view illustrating a schematic diagram of an example of an all-solid-state battery. As shown in FIG. 1, the all-solid-state battery 10 includes a positive electrode layer 11, a negative electrode layer 12, and a solid electrolyte layer 13 interposed between the positive electrode layer 11 and the negative electrode layer 12.
[0151] The positive electrode layer 11 and the negative electrode layer 12 are each layered, particularly sheet-shaped, and contain a solid electrolyte and an electrode active material, and the solid electrolyte layer 13 is layered, particularly sheet-shaped, and contains a solid electrolyte.
[0152] At least one of the positive electrode layer 11, the negative electrode layer 12, and the solid electrolyte layer 13 contains the resin material for a solid battery of the present invention as a solid electrolyte.
[0153] In particular, it is preferable that at least the solid electrolyte layer 13 contains the resin material for a solid battery of the present invention, and it is more preferable that both the positive electrode layer 11 and the solid electrolyte layer 13 contain the resin material for a solid battery of the present invention.
[0154] The active material contained in the positive electrode layer 11, i.e., the positive electrode active material, is usually an inorganic material. More specifically, the positive electrode active material is, for example, LiCoO2, LiNiO2, LiMn2O4, Li2Mn2O3, LiCr 0.5 Mn 0.5 Examples of the positive electrode active material include fluorides such as LiFeF3, LiBH4, Li4BN3H, and the like. 10 boron complex compounds such as boron fluoride complexes, iodine complex compounds such as polyvinylpyridine-iodine complexes, and nonmetallic compounds such as sulfur can also be used.
[0155] The active material contained in the negative electrode layer 12, i.e., the negative electrode active material, is usually an inorganic material. More specifically, examples of the negative electrode active material include Nb2O5, V2O5, TiO2, In2O3, ZnO, SnO2, NiO, ITO, AZO, GZO, ATO, FTO, and Li4Ti5O 12Examples of the negative electrode active material include metal oxides such as Li2Ti3O7, and metal sulfides. Examples of the negative electrode active material include metals and alloys such as Li, Al, Si, Si-Mn, Si-Co, Si-Ni, Sn, Zn, Sb, Bi, In, and Au, carbon materials such as graphite and hard carbon, and LiC 24 Alternatively, a material in which lithium ions are inserted between layers of a carbon material such as LiC6 may be used.
[0156] The resin material for solid batteries of the present invention has excellent ionic conductivity by itself and also has excellent adhesion to inorganic materials, and therefore can provide excellent adhesion between the resin material for solid batteries of the present invention and the above-mentioned active materials in contact with the resin material for solid batteries, and can effectively prevent unintended poor adhesion, peeling, and the like between them, and can provide the all-solid-state battery 10 with excellent ionic conductivity that is stable over a long period of time.
[0157] In addition, a current collector (not shown) may be provided on the surface of the positive electrode layer 11 opposite to the surface facing the solid electrolyte layer 13, and on the surface of the negative electrode layer 12 opposite to the surface facing the solid electrolyte layer 13.
[0158] The current collector is usually made of an inorganic material as described below. When the portion in contact with the current collector made of such an inorganic material, i.e., the positive electrode layer 11 or the negative electrode layer 12, is made of a material containing the resin material for a solid battery of the present invention, the adhesion between the portion and the current collector can be improved, and the reliability of the all-solid-state battery 10 can be improved.
[0159] The current collector is a conductor provided to transfer electrons to and from the positive electrode layer 11 and the negative electrode layer 12. The current collector is usually made of a material that has a sufficiently small electrical resistance and whose electrical conductivity characteristics and mechanical structure do not change substantially due to charging and discharging. Specifically, for example, Al, Ti, Pt, Au, Cu, etc. are preferably used, and alloy materials such as stainless steel are also preferably used depending on the application. The shape of the current collector is not particularly limited, and examples thereof include a foil, a plate, a mesh, and the like.
[0160] The all-solid-state battery 10 may be used for any purpose. Examples of electronic devices to which the all-solid-state battery 10 is applied as a power source include mobile phones, smartphones, tablet terminals, video cameras, calculators, electronic game devices, personal computers, digital cameras, and the like. The all-solid-state battery 10 may also be applied to, for example, moving objects such as automobiles. More specifically, the all-solid-state battery 10 can be suitably applied to, for example, storage batteries for electric vehicles, plug-in hybrid vehicles, hybrid vehicles, fuel cell vehicles, and the like. The all-solid-state battery 10 can also be applied to, for example, household power sources, industrial power sources, solar power storage batteries, and the like.
[0161] Although a preferred embodiment of the present invention has been described above, the present invention is not limited to the above, and modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention.
[0162] For example, the present invention is not limited to being applied to the all-solid-state battery described above. More specifically, for example, the battery of the present invention may be a battery other than an all-solid-state battery, such as a fuel cell or a redox flow battery. EXAMPLES
[0163] The present invention will be described in detail below based on examples, but the present invention is not limited thereto.
[0164] [5] Manufacturing of resin materials for solid-state batteries (Example A1) Into a 300 mL three-neck flask equipped with a thermometer, a nitrogen gas inlet tube, and a cooling tube, 65.91 g of norbornene-2-propionic acid ethyl ester, which is the compound represented by the above formula [VI] (wherein m in formula [VI] is 2), 74.63 g of polyethylene glycol monomethyl ether 220, 2.45 g of zinc acetate, and 1.50 g of 1,4-diazabicyclo[2.2.2]octane were weighed out.
[0165] Then, stirring was started with a magnetic stirrer, and the temperature was raised to 130°C while flowing N2. After reaching 130°C, stirring was continued for another 48 hours. The evaporated by-products during stirring were distilled off using a Dean-Stark separator.
[0166] After stirring, the mixture was cooled to room temperature to obtain 122.25 g of reaction liquid A. The solid matter precipitated in reaction liquid A was removed by pressure filtration to obtain 106.17 g of reaction liquid B.
[0167] Next, 106.17g of reaction solution B and 24.48g of aluminum silicate were added to a 300mL three-neck flask equipped with a thermometer, a nitrogen gas inlet tube, and a cooling tube, and stirring was started with a magnetic stirrer. After that, the temperature was raised to 95°C while flowing N2, and after reaching 95°C, stirring was continued for another hour.
[0168] Next, the temperature was lowered to 35° C., and after reaching 35° C., 1.36 g of calcium hydroxide was added and stirred for 1 hour. Next, 210 g of toluene was added, and the mixture was stirred for an additional 5 minutes.
[0169] Thereafter, solid matter was removed by suction filtration to obtain 310.54 g of reaction liquid C. Next, in order to remove the solvent in reaction liquid C, evaporation was carried out at 40° C. for 0.5 hour and at 60° C. for 0.5 hour to obtain reaction liquid D: 93.32 g.
[0170] Into a 300 mL round-bottom flask were placed 93.32 g of reaction solution D, 1.22 g of calcined diatomaceous earth, and a stirring stone, and the mixture was stirred at room temperature for 1 hour using a magnetic stirrer.
[0171] After the stirring was completed, the solid matter was removed by pressure filtration to obtain 89.44 g of reaction solution E. The reaction solution E thus obtained contains the compound represented by the above formula [I] (wherein m is 2, n is 4, and R 1 is a methyl group; and m is 2, n is 5, and R1 is a methyl group) and a compound represented by the above formula [VI] (wherein m is 2).
[0172] The above reaction solution E (10.06 g) was dissolved in toluene (27.89 g), and the solution was charged into a reaction vessel.
[0173] The solution was sparged with nitrogen for 30 minutes to remove oxygen and then heated to 60°C. Once the solution reached 60°C, a solution of 0.3657 g (0.75 mmol) of (η6-toluene)Ni(C6F5)2 in 6.9485 g of toluene (prepared in the glove box) was added to the reaction vessel via syringe. The mixture was stirred at 60°C for 3.0 hours, after which 45.61 g of ethyl acetate was added via syringe. Then, 0.34 g (18.85 mmol) of a 30 wt% aqueous solution of H2O2 was added, and the solution was brought to 50°C.
[0174] Next, the above reaction mixture was treated with 2.65 g (44.13 mmol) of acetic acid and 5.15 g (285.79 mmol) of 30 wt% aqueous H2O2 solution to remove Ni residues, and then washed with water and isopropyl alcohol (IPA).
[0175] The solvent was then removed by evaporation using a rotary evaporator to obtain a polymerization reaction product. The polymerization reaction product was dissolved in the same mass of acetone, and then added to a 14-fold excess amount of heptane and stirred to remove unreacted monomers.
[0176] The product obtained in the above step was dried in a vacuum at 60° C. for 16 hours to obtain, as a monomer component, the compound represented by the above formula [I] (wherein m is 2, n is 4, and R 1 is a methyl group, and compounds in which m is 2, n is 5, and R 1 A resin material for a solid-state battery, comprising a compound represented by the above formula [VI] (wherein m is a methyl group) and a compound represented by the above formula [VI] (wherein m is 2), was isolated in an amount of 5.81 g.
[0177] The resin material for solid-state batteries obtained as described above had a weight average molecular weight of 253,000, a number average molecular weight of 106,000, an average degree of polymerization of 265, and a softening point of 45° C. In addition, the proportion X of the monomer represented by the above formula (I) in the resin material for solid-state batteries was NB is 86 mol%, and the proportion X of the monomer represented by the above formula [VI] VI was 14 mol%.
[0178] (Examples A2 to A4) The resin materials for solid-state batteries were produced in the same manner as in Example A1, except that the reaction conditions were changed so that the constituent monomers, weight average molecular weight, number average molecular weight, and softening point conditions were as shown in Table 1.
[0179] (Comparative Example A1) Polyethylene oxide dimethyl ether having a weight average molecular weight of 2,000 was prepared and used as the resin material for a solid-state battery in this comparative example.
[0180] (Comparative example A2) First, 15.24 g (48.48 mmol) of the compound represented by the following formula [III] was dissolved in a mixed solvent of 135.64 g of toluene and 144.57 g of ethyl acetate, and the solution was filled into a reaction vessel.
[0181] [ka]
[0182] The solution was sparged with nitrogen for 30 minutes to remove oxygen and then heated to 60° C. Once the solution reached 60° C., a solution of 0.470 g (0.97 mmol) of (η6-toluene)Ni(C6F5)2 in 8.93 g of toluene (prepared in the glove box) was added to the reaction vessel via syringe. The mixture was stirred at 60° C. for 2.0 hours, after which 0.44 g (24.24 mmol) of a 30 wt % aqueous solution of H2O2 was added and the solution was brought to 50° C.
[0183] Next, the above reaction mixture was treated with 17.71 g (294.9 mmol) of acetic acid and 34.50 g (1014.1 mmol) of 30 wt% aqueous H2O2 solution to remove Ni residues, and then washed with water and isopropyl alcohol (IPA).
[0184] Next, the solvent was removed by evaporation using a rotary evaporator to obtain a polymerization reaction product containing a polymer represented by the following formula [VIII] and unreacted monomers. The polymerization reaction product was dissolved by adding the same mass of acetone, and then added to a 14-fold excess amount of heptane and stirred to remove the unreacted monomers.
[0185] The acetone solution of the product obtained in the above step was dried in vacuum at 60° C. for 16 hours to isolate 5 g (yield: 33%) of a resin material for solid electrolytes represented by the following formula [VIII].
[0186] [ka]
[0187] The thus obtained resin material for a solid electrolyte had a weight average molecular weight of 16,400, a number average molecular weight of 11,600, an average degree of polymerization of 37, and a softening point of -21°C.
[0188] [6] Production of resin material composition for solid electrolyte (Example B1) 100 parts by mass of the resin material for solid batteries obtained in Example A1, 30.2 parts by mass of Li(CF3SO2)2N(LiTFSI) as a lithium salt, and acetonitrile as a solvent were mixed to obtain a transparent liquid. Then, the liquid was vacuum dried at 60°C for 1 hour to remove acetone, and a resin material composition for solid electrolytes was obtained.
[0189] (Examples B2 to B4) A resin material composition for a solid electrolyte was produced in the same manner as in Example B1, except that the resin material for a solid battery of Example A1 was replaced with the resin materials for a solid battery of Examples A2 to A4, respectively.
[0190] (Comparative examples B1 and B2) A resin material composition for a solid electrolyte was produced in the same manner as in Example B1, except that the resin material for a solid battery of Example A1 was replaced with the resin materials for a solid battery of Comparative Examples A1 and A2, respectively.
[0191] [7] Evaluation [7-1] Ionic conductivity evaluation
[0192] Using each of the solid electrolyte resin material compositions of Examples B1 to B4 and Comparative Examples B1 and B2, the ionic conductivity was evaluated as follows.
[0193] That is, for each of the solid electrolyte resin material compositions of Examples B1 to B4 and Comparative Example B2, the solid electrolyte resin material composition was formed into a sheet by vacuum pressing at 0.8 MPa and 100° C. for 5 minutes, and then vacuum dried at 60° C. for 15 hours to remove moisture, thereby obtaining a sample sheet. The sample sheets thus obtained all had a residual solvent amount of 0.1 mass % or less and a moisture amount of 500 ppm or less.
[0194] Using the obtained sample sheet, the ionic conductivity was measured by an AC impedance method at temperatures of 60° C., 45° C., 30° C., and 15° C. The measured frequency range was 1 Hz to 50 kHz, and the measurement was performed at a voltage of 0.5 V.
[0195] On the other hand, for the resin material composition for solid electrolyte of Comparative Example B1, the ion conductivity was measured in the same manner as above, without forming the resin material composition for solid electrolyte into a sheet by vacuum pressing or removing moisture by vacuum drying, and using the resin material composition for solid electrolyte obtained in the above [6] instead of a sample sheet.
[0196] [7-2] Heat resistance The resin materials for solid state batteries of Examples A1 to A4 and Comparative Examples A1 and A2 were used to evaluate the heat resistance as follows.
[0197] That is, using STA7200RV (Hitachi High-Technologies Corporation), each sample of resin material for solid-state batteries was heated in a nitrogen atmosphere from room temperature to 500°C at a heating rate of 10°C / min, and the temperatures at which the weight loss of the sample was 1% and 5% were determined. The higher these temperatures, the better the heat resistance.
[0198] Table 1 shows the conditions of the resin material for solid batteries of Examples A1 to A4 and Comparative Examples A1 and A2, and the results of [7-2] above, and Table 2 shows the configurations of the resin material compositions for solid electrolytes of Examples B1 to B4 and Comparative Examples B1 and B2, and the results of [7-1] above. In Table 2, the ratio of the resin material for solid batteries and the lithium salt in the resin material composition for solid electrolytes is shown as "[O] / [Li]" which is the ratio of the total number of oxygen atoms contained in the resin material for solid batteries contained in the resin material composition for solid electrolytes to the total number of lithium atoms contained in the lithium salt contained in the resin material composition for solid electrolytes, and the ratio by mass of the content of the resin material for solid batteries to the content of the lithium salt in the resin material composition for solid electrolytes is shown as "mass ratio".
[0199] [Table 1]
[0200] [Table 2]
[0201] As is clear from Tables 1 and 2, the present invention provided better results than the comparative examples.
[0202] In addition, the value of m of the constituent monomer represented by the above formula [I] constituting the resin material for solid batteries is variously changed within a range of 0 to 4, and the value of n of the constituent monomer represented by the above formula [I] constituting the resin material for solid batteries is variously changed within a range of 4 to 10, and the proportion X of the constituent monomer represented by the above formula [I] in the resin material for solid batteries is NB [mol%] and the proportion X of the constituent monomer represented by the above formula [VI] VI [mol%] ratio X VI / X NB The weight average molecular weight of the resin material for solid batteries was changed within a range of 100,000 or more and 500,000 or less, the average degree of polymerization was changed within a range of 100 or more and 800 or less, and the softening point was changed within a range of -20°C or more and 100°C or less. Except for this, the resin material for solid batteries and the resin material composition for solid electrolytes were produced in the same manner as in the above Examples and evaluated in the same manner as above, and excellent results were obtained as above.
[0203] In addition, resin material compositions for solid electrolytes were produced in the same manner as in the above Examples, except that the ratio of the total number of oxygen atoms contained in the resin material for solid batteries contained in the resin material composition for solid electrolytes to the total number of lithium atoms contained in the lithium salt contained in the resin material composition for solid electrolytes was variously changed within the range of 4.0 to 33.3, and evaluations were performed in the same manner as above, and excellent results were obtained as above.
[0204] In addition, solid electrolyte resin material compositions were produced in the same manner as in the above Examples, except that LiSCN, LiN(CN)2, LiClO4, LiBF4, LiAsF6, LiPF6, LiCF3SO3, Li(CF3SO2)3C, LiSbF6, Li(FSO2)2N, LiC4F9SO3, LiN(SO2CF2CF3)2, LiPF3(CF2CF3)3, LiPF3(C2F5)3, LiPF3(CF3)3, LiCl, LiF, LiBr, LiI, LiB(C2O4)2, lithium difluoro(oxalate)borate, and lithium bis(oxalate)borate were used as the lithium salt contained in the solid electrolyte resin material composition instead of Li(CF3SO2)2N, and evaluation was performed in the same manner as above, and excellent results were obtained as above.
[0205] In addition, the solid electrolyte resin material compositions of Examples B1 to B4 were used to manufacture the all-solid-state batteries shown in FIG. 1. It was confirmed that all of the batteries exhibited excellent charge / discharge characteristics stably over a wide temperature range and had excellent reliability. [Explanation of symbols]
[0206] 10: All-solid-state battery 11: Positive electrode layer 12: Negative electrode layer 13: Solid electrolyte layer
Claims
1. The main chain has a structure derived from norbornene, A resin material for a solid-state battery, comprising an ethylene oxide structure in a side chain, and an ester structure provided between the norbornene-derived structure and the ethylene oxide structure.
2. The resin material for a solid battery according to claim 1 , comprising a monomer component represented by the following formula (NB): 【Chemistry 1】 (In formula (NB), R 1 is a hydrogen atom or a hydrocarbon group, R 2 , R 3 and R 4 are each independently a hydrogen atom or an organic group having 1 to 3 carbon atoms, m is an integer of 0 to 4, n is an integer of 1 or more, 1 is 0, 1 or 2.)
3. The resin material for a solid battery according to claim 2, which contains a monomer component represented by the following formula [VI] in addition to the monomer component represented by the above formula (NB): 【Chemistry 2】 (In formula [VI], m is an integer of 0 to 4.)
4. The ratio of the monomer represented by the above formula (NB) in the resin material for solid-state batteries is X NB [mol %], the proportion of the monomer represented by the above formula [VI] is X VI When expressed as [mol %], 0.1 / 99.9≦X VI / X NB The resin material for a solid-state battery according to claim 3, which satisfies a relationship of ≦30 / 70.
5. 5. The resin material for a solid-state battery according to claim 1, having a weight average molecular weight of 100,000 or more and 500,000 or less.
6. 5. The resin material for a solid-state battery according to claim 1, having an average degree of polymerization of 100 or more and 800 or less.
7. 5. The resin material for a solid battery according to claim 1, having a softening point of -20°C or higher and 100°C or lower.
8. A resin material comprising a monomer component represented by the following formula [VII]: 【Chemistry 3】 (In formula [VII], n is 4 or 5.)
9. A resin material composition for a solid electrolyte, comprising the resin material for a solid battery according to claim 1 and a lithium salt.
10. The lithium salt is LiSCN, LiN(CN) 2 , LiClO 4 , LiBF 4 , LiAsF 6 , LiPF 6 , LiCF 3 SO 3 , Li(CF 3 SO 2 ) 2 N, Li(CF 3 SO 2 ) 3 C, LiSbF 6 , Li(FSO 2 ) 2 N, LiC 4 F 9 SO 3 , LiN(SO 2 CF 2 CF 3 ) 2 , LiPF 3 (CF 2 CF 3 ) 3 , LiPF 3 (C 2 F 5 ) 3 , LiPF 3 (CF 3 ) 3 , LiCl, LiF, LiBr, LiI, LiB(C 2 O 4 ) 2 10. The resin material composition for solid electrolytes according to claim 9, wherein the compound is at least one selected from the group consisting of lithium difluoro(oxalato)borate and lithium bis(oxalato)borate.
11. 10. A resin material composition for a solid electrolyte according to claim 9, wherein a ratio of a total number of oxygen atoms contained in the resin material for a solid battery contained in the resin material composition for a solid electrolyte to a total number of lithium atoms contained in the lithium salt contained in the resin material composition for a solid electrolyte is 4.0 or more and 33.3 or less.
12. A sheet material comprising a material containing the resin material for a solid-state battery according to claim 1 .
13. A positive electrode layer; A negative electrode layer; a battery comprising an electrolyte layer located between the positive electrode layer and the negative electrode layer, A battery comprising the resin material for a solid battery according to claim 1 .
Citation Information
Patent Citations
All-solid-state battery
WO2014002858A1